Correction: Zero-thermal-quenching and photoluminescence tuning with the assistance of carriers from defect cluster traps. Issue 35 (21st August 2019) - Chen, Yali; Yu, Binxun; Gou, Jing; Liu, Shengzhong Frank
Abstract : Correction for 'Zero-thermal-quenching and photoluminescence tuning with the assistance of carriers from defect cluster traps' by Yali Chen et al., J. Mater. Chem. C, 2018, 6, 10687–10692.